Bioassay and molecular detection of insecticides resistance of Aedes aegypti, vector of dengue in Central Java Province, Indonesia - SAYONO SAYONO; ULFA NURULLITA; WAHYU HANDOYO; WINDA SEPTY TYASNINGRUM; IRFANUL CHAKIM; ANTO BUDIHARJO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sayono, Nurullita U, Handoyo W, Tyasningrum WS, Chakim I, Budiharjo A. 2023. Bioassay and molecular detectionsof insecticides resistance of Aedes aegypti, vector of dengue in Central Java Province, Indonesia. Biodiversitas 24: 300-307. The emergence of insecticide-resistant strains among Aedes aegyptipopulations hampered Dengue control programs in the endemic areas. Moreover, to understand the current situation and distribution of insecticide resistance status of Ae. aegypti to cypermethrin, malathion, and temephos compounds, we conducted morphological and molecular detection in the Dengue endemic areas in Central Java Province, Indonesia. Mosquito larvae were obtained from thirteen villages of five Dengue endemic areas representing different altitudes. Larval and adult stage of Ae. aegypti colony from each village was subjected to a bioassay test based on the WHO procedures. Subsequently, they were sampled and subjected to molecular analysis to identify the 1016G kdr allele using the allele-specific polymerase chain reaction (AS-PCR). Mortality of Ae. aegypti after exposure to cypermethrin, malathion, and temephos ranged from 16-86%, 75-100%, and 6-51%, respectively. These findings showed that Ae. aegypti populations were resistant to cypermethrin and temephos, although malathion-susceptible strains were found among 23.08% of the different altitudinal localities. The result of the AS-PCR indicated that the homozygous (G/G) and heterozygous (V/G) alleles of codon 1016 of the AaNav gene were found throughout the study site altitudes. The development of multiple resistance strains was found among Ae. aegypti populations in Central Java Province, Indonesia. The use ofcypermethrin and temephos compounds must be delayed for at least five years, while malathion can still be used selectively to control the Ae. aegypti population in several areas, namely Karangjati, Gebugan (Semarang District), and Rowosari in Semarang City.